IOT BASED HEALTH MONITORING SYSTEM WITH EEG ANALYSIS - Pranita Narayan Borude; Prof. A.M. Rawate (International Journal of Innovations in Engineering Research and Technology, 2021)
Paralysis is one of the main breakdowns that lead to loss of movement of one or more muscles of the body, which depending on the cause, can affect a particular muscle group or area of the body or a larger area may be involved. In search of rehabilitation, the eye can be regarded as one from organs that can help paralyzed people communicate correctly. Eye movement can be used by paralyzed patients and people without arms to perform simple tasks.This project illustratesthe acquisition and analysis of eye blinking signals to activate devices for patients with paralysis. The method proposed here uses the minimum number of electrodes to produce signals, thereby reducing the occurrence of artifacts, and also after a simple circuit for performing the signal conversion, which is also advantageous from the user’s point of view.